Identifying and Preventing Medical Errors in Patients With Limited English Proficiency: Key Findings and Tools for the Field. Issue 3 (16th March 2014) - Wasserman, Melanie; Renfrew, Megan R.; Green, Alexander R.; Lopez, Lenny; Tan‐McGrory, Aswita; Brach, Cindy; Betancourt, Joseph R.
Abstract Since the 1999 Institute of Medicine (IOM) report To Err is Human, progress has been made in patient safety, but few efforts have focused on safety in patients with limited English proficiency (LEP). This article describes the development, content, and testing of two new evidence‐based Agency for Healthcare Research and Quality (AHRQ) tools for LEP patient safety. In the content development phase, a comprehensive mixed‐methods approach was used to identify common causes of errors for LEP patients, high‐risk scenarios, and evidence‐based strategies to address them. Based on our findings, Improving Patient Safety Systems for Limited English Proficient Patients: A Guide for Hospitals contains recommendations to improve detection and prevention of medical errors across diverse populations, and TeamSTEPPS Enhancing Safety for Patients with Limited English Proficiency Module trains staff to improve safety through team communication and incorporating interpreters in the care process. The Hospital Guide was validated with leaders in quality and safety at diverse hospitals, and the TeamSTEPPS LEP module was field‐tested in varied settings within three hospitals. Both tools were found to be implementable, acceptable to their audiences, and conducive to learning. Further research on the impact of the combined use of the guide and module would shed light on their value as a multifaceted intervention.